The hurricane sisters : a novel - Frank, Dorothea Benton (Frank, Dorothea Benton. Lowcountry tales., 2014)
"Best friends since the first day of classes at The College of Charleston, Ashley Anne Waters and Mary Beth Smythe, now 23 years old, live in Ashley's parents' beach house rent-free. Ashley is a gallery assistant who aspires to become an artist. Mary Beth, a gifted cook from Tennessee, works for a caterer while searching for a good teaching job. Though they both know what they want out of life, their parents barely support their dreams and worry for their precarious finances. While they don't make much money, the girls do have a million-dollar view that comes with living in that fabulous house on Sullivans Island. Sipping wine on the porch and watching a blood-red sunset, Ashley and Mary Beth hit on a brilliant and lucrative idea. With a new coat of paint, the first floor would be a perfect place for soireés for paying guests. Knowing her parents would be horrified at the idea of common strangers trampling through their home, Ashley won't tell them. Besides, Clayton and Liz Waters have enough problems of their own. A successful investment banker, Clayton is too often found in his pied-à-terre in Manhattan--which Liz is sure he uses to have an affair. And when will Ashley and her brother, Ivy, a gay man with a very wealthy and very Asian life partner--ever grow up? Then there is Maisie, Liz's mother, the family matriarch who has just turned eighty, who never lets Liz forget that she's not her perfect dead sister, Juliet. For these Lowcountry women, an emotional hurricane is about to blow through their lives, wreaking havoc that will test them in unexpected ways, ultimately transforming the bonds they share" --